Osteogenic Potential Reduction in Mesenchymal Stem Cells under Prolonged Simulated Microgravity - A.Y. Ratushnyy; O.V. Grigorieva; L.B. Buravkova (Учёные записки Казанского университета: Серия Естественные науки)
Increasing the duration of orbital space flights up to 6–12 months and planning interplanetary missions actualizes the need for a better understanding of the mechanisms of osteopenia caused by microgravity. Investigation of mesenchymal stem cells (MSCs) that support the tissue homeostasis under microgravity conditions allows a deeper insight into the processes underlying bone loss. The purpose of this study was to investigate the osteogenic potential of MSCs under prolonged simulated microgravity by clinorotation. Using the method of mineralized matrix detection, it has been found that MSCs osteogenic potential decreased after long-term clinorotation. The investigation of major osteogenic gene expression has showed decreased transcriptional activity in RUNX2, ALPL-1, Col-1, but increased expression of PPARγ. One of the reasons for the decreased osteogenic potential of MSCs may be an increased level of reactive oxygen species (ROS) after 30 days of clinorotation. ROS may affect cellular signaling cascades, such as Wnt, Hedgehog and FOXO pathways, thereby leading to a shift of the differentiation potential to adipogenesis.